The Influence of Professional Development and Communication Skills on Teaching Performance of Higher Education Lecturers on Brunei Darussalam - Munohsamy @ Munasamy, Thulasimani (2022)
In this 21st century, communication skills, development of educators and the teaching performances of the educators have become very important and major contribution to the education field. Educators are anticipated to accommodate to changes and advance their skills, which are expected to directly enrich the students’ achievement and the education quality. In reality, lifelong skills such as effective communication skills are compulsory for educators to send their messages across to students and their colleagues. Effective communication skills and professional development is expected to accelerate the teaching performances of an educator. This straightaway increases the teaching quality thus student’s achievement. Therefore, the objective of this research is to study the influence of professional development and communication skills towards teaching performance of university lecturers in Negara Brunei Darussalam. This is a quantitative study. In order to fulfill the purpose of this research, a survey was created and distributed to the lecturers in Brunei universities. The data of the study was analyzed using Statistical Package for the Social Sciences (SPSS). The mean of the three variables were measured. Pearson Chi Square, Pearson Correlations and regression was used to obtain the results. The findings revealed that there is difference the mean score of the three variables, there is a significant difference in professional development, communication skills and teaching performance attributing to gender. The results also revealed that there is no correlation between the three variables with regards to age and also the number of years of teaching experience of the lecturers. Besides that, the findings of the study revealed that there is correlation between professional development, communication skills and teaching performances itself. Even though, there is a difference in the level as perceived by the respondents in this study, however it is found to be positively bringing significance to the study. Based on the respondent’s perception, professional development is more dominant variable than communication skills in terms of their influence towards teaching performance. Therefore, it is suggested that every educator has to improve themselves through professional development programme internally and externally for their benefit, schools’ benefit and benefit of the students directly. The contribution to the field of education and community will be very significant with the benefit gained through the professional development programmes and the usage of effective communication skills by the educators.